Pemeliharaan Mesin Hydraulic Shear Menggunakan Pendekatan Reliability Centered Maintenance dan Manajemen Suku Cadang - Faisal Mustaqim; Wilson Kosasih; Ahmad Ahnad (Universitas Katolik Parahyangan, 2020)
Production equipment that has a high operating time becomes a vital aspect in supporting the operational system, and its maintenance becomes a critical point that must be planned. This research discusses maintenance policies that focus on machine reliability and parts availability to produce proper maintenance actions, optimal maintenance scheduling and good spare-parts management. The research was conducted on a developing manufacturing company engaged the field of agricultural aids in the city of Bekasi. This study focused on hydraulic shear machines because they have the largest downtime value of 8,344.8 minutes. This problem has a negative impact on the company because it can reduce the yield. Based on these conditions, the study was conducted using the Reliability Centered Maintenance method to update the maintenance patterns and Poisson Process to determine the number of component requirements needed for the next one year. The data obtained in the form of historical damage to the machine, component cost, labor cost and production cost. This research produces an optimal preventive replacement time interval that is every 154 hours for the oil seal component, 242 hours for the shear blade component, and 324 hours for the oil hydraulic hose (1/2